Pengaruh Metode Pelatihan Simulasi Terhadap Pengetahuan Dan Kinerja Kader TBC YABHYSA Di Kabupaten Sumenep Tahun 2022 - Zetiawan Trisno (Jurnal Ventilator, 2023)
Tuberculosis cases in Indonesia are ranked second in the world. TB prevention needs to be done at the grassroots level by involving trained TB cadres. The simulation training method is one of the strategies in increasing the capacity of cadres in increasing TB knowledge and the performance of TB cadres in finding cases. The purpose of this study was to determine the effect of providing simulation training methods on the level of cadre knowledge and performance of YABHYSA Sumenep TB cadres. This study uses a quantitative analytic survey with a cross-sectional design research design. Sampling using non probability sampling by means of purposive sampling, namely all active cadres SSR YABHYSA Sumenep as many as 45 people.The results showed that there was an effect of providing simulation training methods on increasing knowledge and performance of TB cadres YABHYSA Sumenep between before and after receiving simulation training (p<0.05). It is concluded that the provision of simulation training methods can improve the knowledge of TB cadres and cadre performance in TB case finding.